New Femininities
XXVII, 336 p.
Keywords: This collection of original essays looks at the way in which experiences and representations of femininity are changing, and explores the possibilities for producing 'new' femininities in the twenty-first century. The volume includes a Preface by leading feminist scholar Angela McRobbie.